OPTIMIZATION OF SATRESNARKOBA'S PERFORMANCE IN THE PREVENTION OF NARCOTICS CRIMES FOR THE STABILIZATION OF MAINTENANCE OF PUBLIC ORDER AND SECURITY IN THE JURISDICTION OF TEGAL CITY POLICE - Edwin Worabay (Advances in Police Science Research Journal, 2022)
The writing of this Final Project aims to find solutions that are the answers to problems that occur in the research place. This writing uses qualitative research methods, where the author as the main instrument conducts research on an object and describes it in writing. The object in this writing is the Tegal Kota Police Drug Reserse Unit.The Tegal Kota Police Drug Reserse Unit conducts investigations, investigations, and development of narcotics crime cases. Activities that are no less important are the prevention of narcotics crimes themselves. But in the implementation of these activities, there are obstacles that hinder them so that they do not run optimally.The author analyzes and evaluates narcotics prevention activities to support the maintenance of public order and security stabilization program which is a priority program for the Head of the Republic of Indonesia Police General Drs. Listyo Sigit Prabowo, M.Si. and maximize satresnarkoba's performance in the prevention of narcotics crimes.